HARNESSING VERBAL ABILITY AND INTERACTION TO TRANSFORM CHILDREN'S LANGUAGE SKILLS IN ENGLISH READ-ALOUD ACTIVITIES - Yusuf, Faidah; Irfan, Muhammad; Handayani, Rifhani; Nur Aeni (UIN Alauddin Makassar, 2025)
This study explores the impact of verbal ability and interaction on children’s language skills during English read-aloud activities. Read-aloud sessions are widely recognized as a pivotal method to enhance children’s cognitive and linguistic development. The research employed a structural equation modeling approach to analyze data from 108 children aged 6 to 9 years participating in interactive English storytelling sessions. Key variables included verbal ability, interaction, and language skill development. Findings reveal that verbal ability significantly influences language skills, with a path coefficient of 0.400 (p = 0.001), underscoring its critical role in vocabulary acquisition and sentence construction. Interaction, though showing a moderate effect (0.185, p = 0.068), highlights the importance of collaborative learning and engagement in strengthening comprehension and contextual language use. Additionally, the response to read-aloud stories demonstrate a meaningful contribution (0.331, p = 0.009), emphasizing the role of narrative exposure in fostering linguistic competence. These findings provide actionable insights for educators and parents, suggesting that incorporating interactive elements and verbal practice into English read-aloud sessions can significantly boost children’s language skills. This research contributes to the growing body of literature on effective language development strategies and emphasizes the importance of creating engaging, communicative learning environments.